1956
DOI: 10.1113/jphysiol.1956.sp005541
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physical properties and in the collagen and hexosamine contents of the foetal membranes during pregnancy in the rat

Abstract: In the course of other work we observed that the foetal membranes (amnion and yolk sac) showed changes in physical properties at the end of pregnancy. From fairly tough, clean and well-defined structures earlier in pregnancy they became soft, friable, slimy and ill defined. These changes seemed likely to be of biological importance in facilitating the birth of the foetus, and we thought it of interest to examine them in more detail. We have now tested the strength of the membranes by measuring the pressure req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Lastly, on Day 21 the specific orientation of collagen bundles seen on Days 18-20 was absent. These structural alterations, which have not been previously described for rat fetal membranes, are consistent with the findings of Harkness and Harkness [12], who reported that weakening of rat fetal membranes was accompanied by a decline in collagen concentration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Lastly, on Day 21 the specific orientation of collagen bundles seen on Days 18-20 was absent. These structural alterations, which have not been previously described for rat fetal membranes, are consistent with the findings of Harkness and Harkness [12], who reported that weakening of rat fetal membranes was accompanied by a decline in collagen concentration.…”
Section: Discussionsupporting
confidence: 92%
“…A single early biochemical and physical study by Harkness and Harkness [12] showed that a decrease in collagen content of rat fetal membranes was accompanied by a decline in their physical strength. The approach these researchers used, however, did not permit a determination of the membrane(s) affected, i.e., VYSP, amnion, or both.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As pregnancy approaches term, the structure of the amnion VYSP changes as a prelude to parturition [1,2]. The amnion becomes a viscous gel, while the VYSP thins, particularly in the capsular region, and ultimately ruptures [2].…”
Section: Introductionmentioning
confidence: 99%
“…1A). deteriorate so that by late gestation it may be considered nonfunctional (9). Concomitant with the VYS decline, the fetal liver begins to increase the synthesis of proteins previously produced by the VYS (23).…”
Section: Resultsmentioning
confidence: 99%